2004
DOI: 10.1016/s0002-9440(10)63769-8
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Apolipoprotein E Expression and Recruitment from Circulation to Modulate Smooth Muscle Cell Response to Endothelial Denudation

Abstract: Apolipoprotein E (apoE) has been shown previously to have anti-proliferative and anti-migratory effects on smooth muscle cells in culture. In addition, overexpression of the apoE gene also reduces neointimal hyperplasia in mice after endothelial denudation. In this investigation, immunohistochemical techniques were used to demonstrate that apoE was present in the medial smooth muscle layers of the carotid artery between 1 and 28 days after endothelial cell denudation. Analysis of transgenic mice overexpressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The next experiment determined whether the suppression of neointimal hyperplasia in FVB/N mice by high circulating levels of apoE that we have reported previously (8) may be attributable to the activation of smooth muscle iNOS expression in this strain as a consequence of the increased recruitment of human apoE to the site of arterial injury (10). We compared apoE recruitment and iNOS expression in injured arteries of FVB/N mice with or without transgenic overexpression of human apoE in the liver.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The next experiment determined whether the suppression of neointimal hyperplasia in FVB/N mice by high circulating levels of apoE that we have reported previously (8) may be attributable to the activation of smooth muscle iNOS expression in this strain as a consequence of the increased recruitment of human apoE to the site of arterial injury (10). We compared apoE recruitment and iNOS expression in injured arteries of FVB/N mice with or without transgenic overexpression of human apoE in the liver.…”
Section: Resultsmentioning
confidence: 95%
“…Transgenic mice with liver-specific human apoE gene expression were generously provided by Dr. John Taylor (Gladstone Institute, San Francisco, CA) and were backcrossed to the FVB/N background in our institution as described previously (8,10). The genotype of the apoE transgenic mice was determined based on the amount of human apoE present in the serum, which averaged ‫ف‬ 30 mg/dl (10). All animals were maintained on a 12 h light/12 h dark cycle and were fed a normal mouse chow diet (Harlan Teklad, Madison, WI).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Smooth muscle cells of artery walls in peripheral tissues express apoE (Majack et al, 1988;Moore et al, 2004), and apoE has been detected in cells along vessels in the CNS by anti-apoE immunostaining (Boyles et al, 1985), but the source was unclear. We demonstrated that apoE is produced in smooth muscle cells in large vessels and in cells surrounding small vessels in the CNS.…”
Section: Discussionmentioning
confidence: 99%